EXPERIENCE IN PRESERVING THE GENETIC DIVERSITY OF STONE FRUITS USING THE BORDER HEDGING TECHNOLOGY - G. V. Eremin; T. A. Gasanova; V. G. Eremin; I. S. Chepinoga (Труды по прикладной ботанике, генетике и селекции)
Conservation of the world’s plant genetic resources is one of the most significant and relevant problems of mankind. At Krymsk Experimental Breeding Station of VIR, where the largest stone fruit plant genetic diversity in Russia is assembled (more than 5 thousand genotypes: cultivars and species, wild forms, distant hybrids and polyploids), a collection maintenance technology of ‘border hedging’ has been developed and successfully used. This method makes it quite economical (in terms of space reduction, simplification of the system of care for the storage garden, and decreasing the use of chemical protection agents) to maintain a large number of live accessions ex situ. The border hedging technology is based on a propagule nursery system that enables plants to grow longer than in conventional gardens, constantly keeping them in a state of active growth. The basic elements of this technology are dense arrangement of plants (intervals for high-growing plants: 4.0–5.0 m between rows, and 1.0–1.5 m in a row; for low-growing ones: 2.5 m between rows, and 0.5–1.0 m in a row) and annual pruning of shoots at a height of 1.0–1.2 m. Years of experience in using a denser planting pattern for collection garden maintenance helped to identify a number of most significant factors in this system, which make up the scientific basis of the technology for optimally efficient preservation of genotypes and their genetic compliance (representativeness). Among them are biological features of the in situ plant growth habit, including vigor, selection of rootstock or decision on own-root cultivation, layout of the plot, and maintenance system. If it is necessary to study the accessions in the garden where they are preserved in order to make their initial evaluation (approbation, morphological description, study of crop structure, biochemical or biotechnological assessment, analysis of resistance to biotic and abiotic stressors), the plants should not be pruned for 1–2 years. Upon completion of these works, the trees are coppiced again.